Privileging Heteronormativity in Alberta’s Comprehensive Health and Sanctioned Religious Curriculum: A Critical Discourse Analysis - Surette, Tanya (Alberta Journal of Educational Research, 2019)
Although recently the Alberta Government has made many efforts and initiatives to promote support for gender and sexual minority students in schools, ongoing disparities exist between the aspirations for safe and inclusive school environments and the hostile reality of life in schools for this population. This article summarizes the results of a critical analysis of provincial core health literacy curricula along with school-sanctioned religious curricula. The article then highlights probable reasons for the ongoing lack of education and support for gender and sexual diversity in schools and suggests possible contributors to the oppressive environment for these students in rural Southern Alberta. Alors que le gouvernement albertain a récemment déployé beaucoup d’efforts et créé plusieurs initiatives pour appuyer les élèves ayant une orientation ou une identité sexuelle minoritaires dans les écoles, des disparités perdurent entre les aspirations visant des milieux scolaires sécuritaires et inclusifs et la réalité hostile que vit cette population dans les écoles. Cet article résume les résultats d’une analyse critique des programmes d’enseignement sur la santé et des programmes d’études religieuses approuvés par les écoles. Par la suite, l’article souligne les raisons qui pourraient expliquer le manque constant d’éducation et d’appui pour la diversité sexuelle et de genre dans les écoles, et propose des facteurs pouvant contribuer à l’environnement oppressant qui existe pour ces élèves dans le sud de l’Alberta. Mots clés : éducation sexuelle; diversité sexuelle et de genre; religion; éducation à la justice sociale